ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PERSEPSI MASYARAKAT TERHADAP PELAKSANAAN VAKSIN COVID-19 WILAYAH KERJA PUSKESMAS TEBAS KABUPATEN SAMBAS - Qois, Alwan Azhar; Maulana, Muhammad Ali; Pramana, Yoga (Department of Nursing, Faculty of Medicine, Universitas Tanjungpura, 2024)
Background: Public perception of the Covid-19 vaccine is a response or acceptance of the information obtained regarding confidence in the halalness of the vaccine, willingness to be vaccinated and the capacity of health workers who administer the Covid-19 vaccine. Methods: This research is a quantitative study using a cross sectional design. The sample of this research was 96 respondents obtained from direct interviews and filling out questionnaires, data analysis used Chi Square. Results: Shows that out of 96 respondents based on Perception of vaccine safety there is a p-value (0,944), Perception of vaccine effectiveness and necessity there is a p-value (0,524), Acceptance of vaccine requirements and schedule there is a p-value (1,000), Positive values and their influence on vaccines there is a p-value (0.477), Perception of legitimacy and authority needed in vaccination there is a p-value (1,000). Conclusion: Public Perception of the Implementation of the Covid-19 Vaccine in the Working Area of the Tebas Health Center in Sambas Regency from the results of a bivariate analysis shows that there is a significant relationship between age, gender, history of Covid-19 disease and the Implementation of the Covid-19 Vaccine in the working area of the Tebas Health Center, Sambas Regency. Keywords: Perception, Vaccines, Covid-19, Risk factors